From a Real Place and Real People: Interview with Mississippi Damned Writer/Director Tina Mabry - Moore, Marlon Rachquel (Black Camera, 2011)
Marlon Rachquel Moore interviews emerging independent filmmaker Tina Mabry about her southern upbringing, racial and sexual consciousness, and the joys and turbulence of bringing her first feature-length film, Mississippi Damned, to the silver screen. Mississippi Damned is based on Mabry's family and set in her hometown of Tupelo, Mississippi.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

On How Queer Cinema Might Feel. - Quinlivan, Davina (Music, Sound, and the Moving Image, 2015)
Examines the soundscapes of Derek Jarman's film "Blue" (1993) and Isaac Julien's video installation 'True north' (2007), and the way they contribute to promoting embodied responses in the viewer. Draws on the writings of Luce Irigaray and Laura U. Marks to explore the relationship between haptic theory and queer spectatorship.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Paris is burning: Intersectionality in 90s Queer Cinema. - Brew, Tara (Film Matters, 2019)
The overlap of marginalised race and sexuality is highlighted in the 1990 documentary "Paris is burning" which depicts the life of New York's black and Latino drag queens. The author offers an analysis of the social circumstances that gave birth to this culture which originated in 1980s Harlem.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

New Queer Cinema 2.0?: Lesbian-focused Films and the Internet. - Beirne, Rebecca (Screen, 2014)
The Internet distribution of lesbian-focused films seen as an example of the ways in which independent producers and distributors are offering their films for sale on the web. Incl. a table comparing costs and number of films available across a range of legal and illegal sites.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

We are here but are we Queer?: Lesbian Filmmaking versus Queer Cinema Conference, London, 12 March 1994 - Florence, Penny (Screen, 1994)
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

The Queer Film Ecosystem: Symbolic Economy, Festivals, and Queer Cinema's Legs. - Damiens, Antoine (Studies in European Cinema, 2018)
Stresses the crucial importance of LGBT festivals in promoting examples of queer cinema throughout Europe and the USA.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Straight Skin, Gay Masks and Pretending to Be Gay on Screen - Padva, Gilad (Routledge, 2020)
Straight  Skin,  Gay  Masks  and  Pretending  to  Be  Gay  on  Screen  examines cinematic depictions  of  pretending-to-be-gay,  assessing  performances  that not only reflect heteronormative and explicitly homophobic attitudes, but also  offer  depictions  of  gay  selfhood with  more  nuanced  multidirectional identifications. The case of straight protagonists pretending to be gay on screen is the ideal context in which to study unanticipated progressivity and dissidence in regard to  cultural  construction  of  human sexualities  in  the  face  of  theatricalized epistemological collapse. Teasing apart the dynamics of depictions of both sexual  stability  and  fluidity  in  cinematic  images  of  men  pretending  to  be gay offers new insights into such salient issues as sexual vulnerability and dynamics  and  long-term  queer  visibility  in  a  politically  complicated  mass culture  which  is  mostly  produced  in  a  heteronormative  and  even  hostile cultural environment. Additionally, this book initially examines queer uses of sexuality masquerade in Alternate Gay World Cinema that allegorically features a world pretending to be gay, in which straights are harassed and persecuted, in order to expose the tragic consequences of sexual intolerance. Films  and  TV  series  examined  as  part  of  the  analysis  include  The  Gay Deceivers, Victor/Victoria, Happy Texas, William Friedkin’s Cruising and many other straight and gay screens. This  is  a  fascinating  and  important  study  relevant  to  students  and researchers in Film Studies, Media Studies, Gender Studies, Queer Studies, Sexuality Studies, Communication Studies and Cultural Studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Coquie Hughes: Urban Lesbian Filmmaker Introduction to Yvonne Welbon’s Interview with Coquie Hughes - Brody, Jennifer Devere (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Toni Morrison purportedly began her career as a novelist because she noticed a dearth of books about black women. As a result of this limitation, Morrison desired to write books “for people like [her], which is to say black people, curious people, demanding people—people who can’t be faked, people who don’t need to be patronized.”¹ Similarly the writer, director, and filmmaker Coquie Hughes (born Latasha Iva Hughes in Chicago in 1970) has produced narratives that feature an array of queer black women—“Girls Like Us” as she calls them in her web series—who are curious, demanding, flawed, and
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Circuitous Route of Presenting Black Butch: The Travels of Dee Rees’s Pariah - Declue, Jennifer (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
At the 2012 Golden Globe awards, during her acceptance speech for the Best Actress award for her performance in The Iron Lady (Phyllida Lloyd, 2012), Meryl Streep gave a shout-out to Adepero Oduye for her role as Alike in Dee Rees’s feature film Pariah (2011). The sentiment behind this esteemed acknowledgment was that brilliant performances in important independent films were overlooked and deserved recognition. Streep would go on to win the Best Actress Oscar for a her portrayal of Britain’s first woman prime minister, the a ultraconservative Margaret Thatcher.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Creating the World Anew: Black Lesbian Legacies and Queer Film Futures - Gumbs, Alexis Pauline (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Deeply grounded in the legacy of Black lesbian artists, writers, and filmmakers, current Black lesbian filmmakers are helping to build infrastructure for a transformed future using deeply interconnected methods to transform the whole world and (while we’re at it) the meaning of life. This chapter looks at two projects, the established and evolving Queer Women of Color Media Arts Project based in San Francisco and the emerging Queer Renaissance and Black Feminist Film School Project based in Durham, North Carolina, as examples of the robust future of Black lesbian filmmaking as a transformative community-building practice. The Queer Women of Color
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Narrating Our History: An Introduction - Harris, Thomas Allen (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Around 1994 or 1995 I came across a call for articles for an anthology to be published by the XII Black International Cinema , documenting ten years of the festival and associated activities, 1986– 95. The request asked for articles and film lists from an international and intercultural group of scholars and filmmakers, and I thought this was an opportunity to document the exciting and pioneering work that was being done by a community of emerging Black lesbian and gay film-and video makers at the time.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Book of Ruins and Desire: Interactive Mechatronic Sculpture - Jennings, Pamela L. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The interactive book is a term heard frequently in reference to early experiments in multimedia production. But how to translate the concept of the book into a medium that has no paper, no pages, remains a challenge. Is not a book an object one holds in one’s hands—the cover affected over time by the acids and oils perspiring from the user’s skin, pages turned down and yellowed, torn or marked up? Research could show that the notion of the traditional book has been challenged throughout history. But this challenge has been accelerated with the growing accessibility of new computer
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Construction of Computation and Desire: Introduction to Yvonne Welbon’s Interview with Pamela L. Jennings - Keeling, Kara (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Early in the following interview, Pamela Jennings explains to Yvonne Welbon that her work gradually expanded from an initial and abiding interest in street photography toward working with and through forms of computational media. Jennings equates her move toward what she describes as “computational-based creative expression” with her growing interest in multimedia throughout the early 1990s, and she uses the term multimedia as a way of marking her work in a variety of different media and her interest specifically in computational media because the formulation computational media was not available to her then. The compelling relationship Jennings narrates between her
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Producing Black Lesbian Media - Moore, Candace (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In interviews the comedian Wanda Sykes describes being a successful black, openly gay woman in Hollywood as akin to being a unicorn. Clearly Sykes is majestic. Yet her joke hinges on a bitter truth: the mainstream media industry grants few women, not to mention lesbians of color, access to power. Despite shifts in the cultural imaginary around civil rights, Hollywood continues to maintain an embarrassing lack of diversity in its labor force, especially at decision-making levels. To battle this long-standing reputation, studios have developed diversity-hiring programs.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Cosmic Demonstration of Shari Frilot’s Curatorial Practice - Rastegar, Roya (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Shari Frilot is a filmmaker and curator whose creative practice has been driven by sustained explorations of sexuality, technology, desire, cosmic and subatomic structures, mixed-raced identity, and chaos. She has often expressed her modus operandi in the following terms: “It’s impossible to see a cloud when you’re in the middle of it. You have to move outside of the cloud to really get a sense of it.” By continually shifting between the outside and inside of a given framework—whether institutional or personal—Frilot has developed keen modes of challenging conventional structures for understanding and engaging the moving image.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Shine Louise Houston: An Interstice of Her Own Making - Stallings, L. H. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
It is the twenty-first century, and there is a black lesbian director and producer making pornography! Porn, a genre of film and media that in the last quarter of the twentieth century many black feminist lesbians viewed as capable only of representing and manifesting violence, abuse, and shame. In this essay I examine one of the early works of the black lesbian filmmaker Shine Louise Houston, In Search of the Wild Kingdom (2007), to explore how and why we have arrived at what is a transition from Blues Legacies and Black Feminisms to Pink and White Productions, and from New
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Birth of a Notion: Toward Black, Gay, and Lesbian Imagery in Film and Video - Parkerson, Michelle (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In mainstream media, gays and lesbians of color are either woefully present or predictably absent. The litany of black gay and lesbian characters in Hollywood films and network television reads like its own form of blackface. They range from the burly, black “bulldagger” as whore house madam in the 1933 film The Emperor Jones (starring Paul Robeson) to the predatory lesbian vamp in Spike Lee’s 1983 She’s Gotta Have It ; from Eddie Murphy’s ultracamp Miss Thing hairdresser on NBC’s Saturday Night Live to the snap! queen duo on Fox TV’s In Living Color. These relentless stereo types are part of
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“Invite Me In!”: Angela Robinson at Hollywood’s Threshold - White, Patricia (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In 2005 Angela Robinson released her spy spoof, D.E.B.S. (2004). Robinson first realized the project as the short film D.E.B.S. (2003) through a training program with POWER UP (Professional Organization of Women in Entertainment Reaching Up), the only 501(c)(3) nonprofit film production company and educational organization for women and the GLBTQ community. In 2005 she also became the second black woman and first black lesbian to direct a studio feature, the Disney film Herbie Fully Loaded starring Lindsay Lohan. This moment marked the beginning of the black lesbian media maker hyphenate as Angela Robinson moved to television and began working on The L Word as a writer, director, and eventually producer. Patricia White's essay in this section, "'Invite Me In!': Angela Robinson at the Hollywood Threshold," offers an in-depth exploration of her career trajectory.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stereotypy, Mammy, and Recovery in Cheryl Dunye’s The Watermelon Woman - Wimbley, Karin D. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The Mammy has been in our field of vision as a popular icon representing black womanhood for more than a century in literature, film, and television and in consumer and material culture.¹ Described as an asexual, rotund slave of older age whose sole responsibility is to take care of her master’s children, Mammy is a beloved character who represents all that is nurturing and maternal. She is dark-skinned and boisterous and thought to have mannish features such as large feet and hands. Mammy wears a large skirt, hiding her sex, and covers her nappy hair with a bandanna or handkerchief.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Queer Times, Black Futures - Kara Keeling (Sexual Cultures, 2019)
Finalist, 2019 Lambda Literary Award in LGBTQ StudiesA profound intellectual engagement with Afrofuturism and the philosophical questions of space and time Queer Times, Black Futures considers the promises and pitfalls of imagination, technology, futurity, and liberation as they have persisted in and through racial capitalism. Kara Keeling explores how the speculative fictions of cinema, music, and literature that center black existence provide scenarios wherein we might imagine alternative worlds, queer and otherwise. In doing so, Keeling offers a sustained meditation on contemporary investments in futurity, speculation, and technology, paying particular attention to their significance to queer and black freedom.Keeling reads selected works, such as Sun Ra's 1972 film Space is the Place and the 2005 film The Aggressives, to juxtapose the Afrofuturist tradition of speculative imagination with the similar “speculations” of corporate and financial institutions. In connecting a queer, cinematic reordering of time with the new possibilities technology offers, Keeling thinks with and through a vibrant conception of the imagination as a gateway to queer times and black futures, and the previously unimagined spaces that they can conjure.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Identités diasporiques; _Nettoyé

Embodied Female Experience Through the Lens of Imagination - Green, Sharon R. (Journal of Analytical Psychology, 2010)
In 1971, I made a film entitled Self Portrait of a Nude Model Turned Cinematographer in which I explore the objectifying ‘male’ gaze on my body in contrast to the subjective lived experience of my body. The film was a radical challenge to the gaze that objectifies woman – and thus imprisons her – which had hitherto dominated narrative cinema. Since the objectification of women has largely excluded us from the privileged phallogocentric discourses, in this paper I hope to bring into the psychoanalytic dialogue a woman's lived experience. I will approach this by exploring how remembering this film has become a personally transformative experience as I look back on it through the lens of postmodern and feminist discourses that have emerged since it was made. In addition, I will explore how this process of imaginatively looking back on an artistic creation to generate new discourses in the present is similar to the transformative process of analysis. Lastly, I will present a clinical example, where my embodied countertransference response to a patient's subjection to the objectifying male gaze opens space for a new discourse about her body to emerge.
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

A Few of My Favourite Things: The Feiticeiro/a as Foundation for ‘Pervert’ Characterisation - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A non-foundationalist construct for the Feiticeiro/a character that assumes neither an essentialist nature nor a determinist set of activities is possible. This does not prescribe a ‘type’ of ‘pervert’ character, but instead delineates an epistemic framing for a Feiticeiro/a character. This chapter explores an etymologically based semiotic approach to character construction that accounts for a Derridean view that language is constituted by binary reciprocal delimitations and for a view of sex as a dereified expression of materialised instances of engagement by sexual subjects, in terms of which sexuality is rendered as an opened-outward and connected function. The chapter further deals with an approach based in an empathic engagement between audiences and Feiticeiro/a characters, which is apposite for audiences identifying with but not necessarily liking characters. The chapter closes the volume’s argument around how transgressive, sexually focused Feiticeiro/a characters might productively be constructed in terms other than of essences and determinist actions, but in terms of ‘meaning’ found in the points of connection between heterogeneous bodily surfaces.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Absenting Heteropatriarchal Discourses: The Invisible ‘Pervert’ - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Conservative discourses remain powerful in contemporary life. These demonise the notion of sexual transgressiveness without helping to give a clear, value neutral definition of what ‘transgressive’ is. Screenwriters attempting to write it into characters are therefore likely to rely on psychiatric epistemologies for sexual ‘perversion’ as framings for subjectivity. Unfortunately, Freudian epistemologies of ‘perversion’ render the psychical subject as invisible through built-in determining comparative reference to heteropatriarchal norms and through distinctions between ‘non-pathological’ and ‘pathological’ definitions. This chapter explores the Freudian constructs that entrench this, together with post-structuralist foundations that might revise the constitution and role of the individual subject (and therefore of filmic characters as facsimiles of real people) as he/she relates to the material world as a physical entity, and as he/she manipulates the discourses to which he/she is subject.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Anthropologically Present ‘Perverts’: Re-instating the Feitiço as the Feiticeiro/a - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A post-humanist lens is useful as a starting-point to remedy the absenting and invisibilising effects of sexological epistemologies for the purposes of conceiving a constitution of ‘pervert’ filmic characters, since certain strains of existential thinking have a meta-theoretical pliancy that is useful for reflecting the non-binary character of complex people beyond simple identity categories, across a range of types and styles of filmic products. If matched with a semiological approach such as that espoused by Barthes, it thereby becomes possible to manipulate signs in the form of character constructions to represent people as more than the sum of their parts and to contain deeper significations that are built into the fabric of their construction. This requires a deeper understanding of the semiotic notion of ‘semes’ as the foundation for character construction. To this end, this chapter explores how sexual ‘perversion’ as reflected in notion of the ‘feitiço’ might serve as a foundation for a new episteme for ‘perverse’ characters, as the Feiticeiro/a as ‘sorcerer/sorceress’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Psychoanalytic Absence: Freudian Object-Focus and the Resultant ‘Pervert Sans-Corpus’ - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The notion of ‘perversity’ suggests inherent transgressiveness. However, a focus on practices does not help identify who filmic characters are in ways that might inform a paradigm for character identity suitable for translation into a visual medium. Failing to achieve this clarity, ‘perverts’ often end up as ‘ambulatory objects’ at once imagined and defined by what is not present. This chapter engages how this manifests in the nineteenth-century sexological discourses that reflected perverse prurience in terms of assumptions that all entities might be empirically identifiable in the same way that material phenomena can be perceived by means of the senses, which is especially visible in the various incarnations of Freudian constructs of ‘fetishism’ that refuse personal agency through reliance on a range of psychodynamic constructs.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Rephrasing Character Action for the Feiticeiro/a: External Coherence Through Transactional Relations - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If character actions are not to be seen in deterministic ways, then an alternative framing should be considered on which writers might base constructs of complexity of action. This is possible if action itself is seen as an expression of relationality rather than as activity-as-substance. Looking at people in this way enables the behaviour of Feiticeiro/a characters to be seen as activities that are more than the actions of combinations of sexed bodies in physical spaces. This chapter explores a construct for action on this basis as it becomes possible by acknowledging in a construct of ‘doing’ the phenomenological notions of ‘being’ as a Feiticeiro/a form constituted by a hybrid of ‘object-discourse-nature-society’ characterised by networks of confluence. The chapter explores the notion of the Feiticeiro/a character in terms of an internal coherency, taking account of interactions and activities (as exhibited through their material form), ‘naturalness’, linearity of course of action and embodied notions of meaning-creation.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Recherche-création; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Rephrasing the Feitiço: A New Episteme for Perverse Characters - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
Interesting and challenging Hollywood-style films that centre on sexually transgressive characters are not easy to script. Many writers fail as a result of an over-valuation of image at the expense of psychologically complex and challenging subjectivity. A hook for exploring the nature of this phenomenon lies in the notion of ‘involving and disturbing’, with a focus on how films might represent it and how audiences might perceive it, and with attention paid to how characters might be constructed. The chapter expands on how this notion of audience engagement might engage with screenwriting as a design function, aimed to construct characters in visual terms yet through words rather than pictures. In addressing certain epistemic limitations to writing character complexity, an alternative epistemic framing for ‘perverse’ characters is considered in terms of characterological ‘is-ness’, philosophical constitution and behaviours and actions.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Feiticeiro/a as a Materially Identifiable Character: Subjectively Conceived Filmic Participants - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a character is to be seen as a structure rather than a substance, the nature of such a structure requires elaboration. If this paradigm is to be internally coherent, a relation of intertwined co-existence between characters and audiences should be built into the framing in ways that provide functional epistemic signposts for mechanisms to translate characters’ intrinsic complexity to these audiences. This chapter approaches this by accounting both for the particularly visual nature of the filmic medium and for how screenplays are not a visual medium themselves and are put to different uses than other forms of narrative writing, therefore requiring distinctive attributes. An orientational notion of relationship between medium and audience is suggested as a foundation for the structure of Feiticeiro/a characters in terms of the philosophical distinction between ‘being’ and ‘appearance’, on the basis of which decisions might be made as to which elements of the character’s constitution should be made apparent and which should either remain invisible or intentionally be obfuscated.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Internally Coherent Feiticeiro/a: A Structure not a Substance - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The categories for ‘perversion’ in the World Health Organization’s ICD fail to describe people and their practices, thereby obscuring the remarkable singularity of individuals and diversity of groups. Instead, they prescribe heteronormative sexual behaviour, which is unhelpful as a foundation for the Feiticeiro/a character. This chapter explores an alternative epistemic construct, as becomes available in the notion of a focalising character, which reflects a ‘semic’ construct that negates the notion of a ‘pervert’ character as a substance, but instead embraces the notion of a Feiticeiro/a character as a structure. The chapter further explores the philosophical nature of this structure as it relates to the thematic elements of a narrative whilst engaging in believable activities in a material world. The chapter then suggests an approach to structure based in a phenomenological notion of the replacement of ‘substance’ with ‘form’/‘structure’ as the foundation of meaning.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Towards an Episteme for the Feiticeiro/a: Realism in Character Construction - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
An episteme for the Feiticeiro/a as a filmic character who is ‘perverse’ needs a form if it is to be useful to writers wanting to construct complex transgressive sexual characters. The beginnings of this framing are productively associated with the semiotic notion of ‘connotation’. This chapter explores what is meant by complexity in character construction and suggests a framing focused on character as an embodied being as a helpful starting-point for an episteme for characterological ‘perversion’. The chapter explores this as a non-foundationalist framing that transcends problematic Cartesian distinctions, concrete object materiality and woolly broad-stroke statements of a disembodied discursive constitution of social and personal experience.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Writing ‘Perverse’ Behaviour for the Feiticeiro/a: Revisioning the ICD Diagnostic Criteria - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a as a psychologically defined and complex character is to be seen as an embodied form/structure (not substance) that exists in dialectical relationships between self, other and discursive constructions of society, a clearer indication should be made about what kinds of behaviours or actions he/she should engage in. This chapter explores how psychiatric diagnostic criteria fail to provide assistance, despite professing to authoritatively mark stable, reliable and accurate epistemic boundaries to sexual activity. The chapter thereby addresses questions of the description of actions versus the demarcation of thoughts, objects, feelings and time as invisible and abstracted notions that are virtually the opposite of what is useful for an episteme for the Feiticeiro/a. It also approaches how the diagnostic criteria codify ‘perverse’ activity in determinist terms, thereby insidiously refusing an epistemic construct of action into which is built an acknowledgement of the behaviours of the Feiticeiro/a as a complex subjectivity.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Cinema's Queer Witness: Ira Sachs's Last Address and the Indifferent View - Rodness, Roshaya (CR: The New Centennial Review, 2019)
Roshaya Rodness is a senior doctoral candidate in the Department of English and Cultural Studies at McMaster University. Her dissertation addresses recent movements in queer theory with a special focus on cinema, poststructuralist ethics, and the nonhuman. She has published in Canadian Literature, Chiasma: A Site for Thought , and World Picture on topics that include contemporary film, indigenous authorship, postcontinental philosophy, and dream theories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Auto-histoires et représentations communautaires dans le cinéma des femmes autochtones - Bertrand, Karine (Canadian Journal of Film Studies, 2020)
In the last decade or so, cinema has revealed itself to be an ideal medium for the transfer and/or remediation of the spoken word as well as stories coming from oral tradition and Indigenous culture. Indeed, cinema is a place of expression which favours cyclical creativity and contributes to the decolonization of stereotyped images propagated by external voices that do not understand the subtleties of languages (real and symbolic) that are anchored in indigenous peoples’ cultural memory. By exploring indigenous cinema as practised by women of diverse nations, this piece demonstrates how cinema can induce the compression and dilation of time, to bring to the audience the fluidity of a story that has been reconfigured according to a new time and carried by spoken words that have chosen to either emancipate themselves from the image or to materialize themselves in it. Furthermore, this article illustrates how a new generation of Indigenous women use cinema to retrace and/or rewrite their personal narrative with the help of autobiographical or collective stories that travel back in time to fill in the blanks left by a fragile memory and to express their will to make peace with a difficult colonial past. Finally, the writings of Lee Maracle (I Am Woman, 1988) and Natasha Kanapé Fontaine (Manifeste Assi, 2014) are being brought forth to show how films such as Suckerfish (Lisa Jackson, 2004) Bithos (Elle-Máijá Tailfeathers, 2015) and Four Faces of the Moon (Amanda Strong, 2016) contribute to the individual and community healing of Indigenous peoples of Canada, through an aesthetic of reconciliation. The exploration of these works, therefore allows us to shed light on and better understand the roles/internal mechanisms of visual autobiographies in the larger context of reconciliation with individual and collective stories/memories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé